Anatomical Variation in the Fissurization of Lung with Embryological and Clinical correlations- A Case Report - Dr. Dinesh Premavathy, M.Sc., Ph.D. (International Journal of Pharma and Bio Sciences, 2021)
Lungs are paired conical organs present in the thoracic cavity, which are responsible for gaseous exchange for oxygenation of blood. Both the lungs are divided into lobes by fissures. The right lung is divided into upper, middle and lower lobes by two fissures. The fissures are horizontal and oblique fissure whereas the left lung is divided into upper and lower lobes by oblique fissure. The left lung is divided into upper and lower lobe by oblique fissure. Both the lungs have ten bronchopulmonary segments (structurally separate and functionally independent units). Embryological evidence showed that the lungs developed from the endodermal counterpart of the foregut. Around 22 days of embryonic period, diverticulum are develop, then between 26-28 days lung buds develop. The right bronchial buds and left bronchial buds are branched into secondary and tertiary buds at 5th and 6th week of embryonic life consecutively. During routine anatomy dissection and demonstration in the Department of Anatomy, a 50 year old male cadaver showed anatomical variation in the right lung. The present study observed that the right lung showed partial horizontal fissure. The reason for partial or incomplete fissure formation is due to incomplete or absence of obliteration of prenatal fissure which indicates partial fusion of lobes, generally fissures separating the broncho-pulmonary segments in prenatal life. The reports says that incomplete fissures of the lung may lead to spread of infection like pneumonia to adjacent lobe and collapse in endobronchial lesions and gradation of the fissures of the lungs are very important for lung surgeries. The present study concludes that the knowledge of anatomical variation of lung is of utmost important in the field of pulmonary medicine.